Effects of Diet and Cyclic Daily Heat Stress on Electrolyte, Nitrogen and Water Intake, Excretion and Retention by Colostomized Male Broiler Chickens - Borges, S.A.; da Silva, A. V. Fischer; Maiorka, A.; Hooge, D.M.; Cummings, K.R. (International Journal of Poultry Science, 2004)
Male Ross broiler chicks were grown in a thermoneutral environment from 0 to 14 d. From 14 to 41 d, half the birds remained in the thermoneutral room (22.5 ± 3.5oC) whereas the other half in another room were exposed daily to cyclic stress (22.5 ± 3.5oC for 14 h and 33 ± 2.0oC for 10 h). Chickens were individually caged from 22 to 41 d, with colostomy at 28 to 30 d, to evaluate effects of heat stress (d 41) and dietary electrolyte balance (DEB = Na + K - Cl mEq/kg) on serum electrolytes and on water, electrolyte and nitrogen retention (18 birds, 9/room with 3/treatment therein). The DEB levels were 140, 240, or 340 mEq/kg. The DEB levels fed from 0 to 41 d were obtained by addition of NaCl and NaHCO3, plus KHCO3 or NH4Cl as needed. Feces and urine were collected separately. Nitrogen balance was least (greatest nitrogen excretion) using 140 mEq/kg in the thermoneutral room. For DEB 240, retention of Na increased compared to DEB 140 in the thermoneutral room (5.24 vs 1.75 mEq/bird/d; P < 0.05) and in the heat stress room (5.29 vs 2.33 mEq/bird/d; P < 0.05). Overall, urine Na and K increased in the 340 compared to the 240 mEq/kg treatment and Cl increased in 140 compared to 240 or 340 mEq/kg treatments. The DEB of 240 was most favorable in either temperature environment based on water, electrolyte and nitrogen metabolism results.